Laboratory Characteristics And Diagnostic Significance Of Antibiotic-Associated Diarrhea In Young Children - Rabbimova Dilfuza Toshtemirovna; Shavdirova Gulbonu Mansurovna (Zien Journals, 2025)
To determine the specific laboratory characteristics of AAD in early childhood and assess the diagnostic value of fecal calprotectin, C-reactive protein (CRP), and coprological parameters in differentiating disease forms.
Keywords: calprotectin; Childhood Diseases; AAD